Wuchiapingian (Lopingian, late Permian) brachiopod fauna from Guangdong Province, southeastern China: systematics and contribution to the Lopingian recovery. (January 2023) - Wu, Huiting; Zhang, Yang; Stubbs, Thomas L.; Chen, Anfeng; Zhai, Pengcheng; Sun, Yuanlin
Abstract: A diverse Wuchiapingian brachiopod fauna, which contains 57 species in 28 genera, is described from the Shuizhutang Formation at the Liannan section, Guangdong province, southeastern China. Four new species Tyloplecta liannanensis n. sp., Linoproductus huananensis n. sp., Araxathyris minor n. sp., and Permophricodothyris flata n. sp. are proposed. From well-preserved Liannan specimens, characteristics of the shell microstructures in Permianella are revised, and different morphologies of muscle scars in Permophricodothyris are distinctly shown. Until now, only several Wuchiapingian brachiopod faunas have been found in South China. Compared with these faunas, the Liannan fauna shows much higher α diversity and is more like faunas from southeastern China than those from the Yangtze area in faunal composition. The Liannan fauna is dominated with Neochonetes, Transennatia, Orthothetina, Permophricodothyris, and Cathaysia, which are normally larger and more strongly ornamented than their Changhsingian counterparts. The Wuchiapingian brachiopods in South China are represented mainly by the Douling fauna and Shuizhutang fauna. The Douling fauna has relatively low diversity and presents the survival stage after the Guadalupian–Lopingian boundary crisis. The Shuizhutang fauna has a much higher diversity and more key Changhsingian taxa and shows a rapid radiation stage. Faunal compositions of the two faunas indicate that the initial recovery of brachiopods occurred mainly at the genus level followed by a more rapid radiation at both genus and species levels. UUID: http://zoobank.org/474cd988-6ec3-4d16-b045-f84d5fe3fb66